The Influence of Financial Distress, Leverage, and Free Cash Flow on Earnings Management - Amalia, Hafizha Azra; Afrizal, Afrizal; Herawaty, Netty (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine the effect of financial distress, leverage, and free cash flow on earnings management in non-bank state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The population in this study were non-bank state-owned companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling method used was the purposive sampling method, obtaining a sample of 18 companies with 4 years of observation. The independent variables in this study are financial distress, leverage, and free cash flow and the dependent variable in this study is earnings management. The data collection method uses secondary data taken from the annual financial reports from the official IDX website www.idx.co.id. This study uses a quantitative approach, and the data analysis method used is statistical analysis and multiple linear regressions using the SPSS computer program. The results of the study indicate that earnings management is influenced by financial distress, leverage, and free cash flow simultaneously. The results of the study indicate that financial distress does not have a significant effect on earnings management, leverage does not have a significant effect on earnings management, and free cash flow has a significant effect on earnings management.